A qualitative analysis of explanatory models in medically unexplained physical symptoms presenting to a tertiary health care psychiatric facility in South India. (November 2016) - Menon, Vikas; Shanmuganathan, Balasubramanian; Babu Arun, Anand; Thamizh, Jaiganesh Selvapandian; Selvakumar, Nivedhitha; Sarkar, Siddharth
Background: Knowledge about subjective perceptions and explanatory models has the potential to inform clinical evaluation and lead to development of patient-friendly treatment models in medically unexplained physical symptoms (MUPS). Aim: To collect qualitative data about explanatory models in MUPS. Methods: A cross-sectional observational study was done among patients with MUPS presenting over a 2-year period to a specialty psychosomatic clinic. The Short Explanatory Model of Illness interview was used to gather qualitative data about explanatory models which were subsequently recoded using standard manuals. Results: A total of 123 subjects were evaluated. The nature of symptoms was most commonly reported as 'non-specific' ( n = 102, 82.9%) but of moderate to severe intensity ( n = 87, 73.8%). Getting cured or showing improvement was the most common expectation from treatment ( n = 58, 47.9%). Moderate to severe impact of symptoms was reported on work output ( n = 100, 84%), emotional life ( n = 85, 71.4%) and physical mobility ( n = 59, 49.1%). A considerable proportion was either dissatisfied ( n = 61, 50%) or frankly unhappy ( n = 38, 31.4%) with treatment received. Conclusion: There is a need to re-calibrate the clinical approach to people with MUPS to enhance treatment satisfaction. Our findings could assist in evolving culturally sensitive conceptualizations of illness and in developing patient-centred models for therapy in MUPS patients.